Sport dependent effects on the multisensory balance integration during upright posture: a comparison between professional horseback riders, judokas and non-athletes - Viseu, J.; Yiou, E.; Morin, P. O.; Olivier, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: It is well-known that postural stability is improved with intensive sport practice (1). The contribution of sensory inputs to balance control also changes, with athletes relying less on vision and more on somesthetic inputs than non-athletes (NA) (2). It is however noteworthy that, in the literature, balance performance and sensory processing are investigated in athletes practising a sport in the standing posture (e.g. judo, soccer etc.). The present study hypothesised that high-level (HL) athletes practicing a sport in the sitting posture (horseback riding) develop specific balance and sensory adaptations. METHODS: Thirty-four HL judokas (JU), 27 HL horseback riders (HR) and 21 NA participated in the experiment. They stood upright on a stabilometric platform (static condition) or on a seesaw device with a mediolateral (ML) or anteroposterior (AP) instability (dynamic conditions). These stability conditions were carried out with eyes opened (EO) or closed (EC). Experimental variables included linear (mean center-of-pressure (CP) velocity (VCP), standard deviation of CP shift along ML (SDX) and AP (SDY) direction) and non-linear parameters (SampEnX and SampEnY, corresponding to ML and AP sample entropy, respectively; these variables reflect the attentional cost of balance, (3)). RESULTS: VCP was significantly lower in both HL groups than in NA under all stability conditions (p<0.05), while SDY was lower in HR than in JU under static and AP dynamic condition (p<0.01). In EO, VCP was lower in HR than in both JU and NA under dynamic conditions (p<0.001). In EC, VCP was lower in JU than in HR and NA under dynamic conditions (p<0.05). Finally, SampEnX was higher in HR than in JU under static condition (p<0.05), while SampEnY was higher in HR than in JU under both static and ML dynamic condition (p<0.01). CONCLUSION: As expected, JU and HR had a better stability than NA under all stability conditions. More originally, results showed that HR relied more on vision to control balance. In addition, entropy variables revealed that JU devoted more attention to control balance than HR. These results suggest that the sensory contribution and attentional cost of balance is sport-dependent, and may depend on the posture adopted by athletes during their practice. These results open up new knowledge on the specificity of balance control in sports and may be useful to select relevant stabilometric variables for the follow-up of HL athletes.